PENGARUH PERBANDINGAN TEPUNG MOCAF (Modified Cassava Flour) DAN TAPIOKA SEBAGAI BAHAN PENGISI TERHADAP SIFAT KIMIA, FISIK, DAN SENSORI NUGGET IKAN BAJI-BAJI (Grammoplites Scaber) - Khoti Jayanti; Erdi Suroso; Sussi Astuti; Novita Herdiana (Jurnal Agroindustri Berkelanjutan, 2023)
Mocaf flour and tapioca have potential as a filler to produce baji-baji fish nuggets. The purpose of this study was to determine the effect of adding mocaf flour and tapioca on chemical, physical and sensory characteristcs of baji-baji fish nuggets, and to obtained the best ratio of mocaf flour and tapioca to produce baji-baji fish nuggets with chemical, physical and sensory properties. The experiment used a Completely Randomized Block Design (RCBD) with a single factor, and four replications.  The factor used was the comparison of mocaf flour and tapioca which consisted of six levels, namely 5%: 95% (P0), 20%: 80% (P1), 35%: 65% (P2), 50%: 50% (P3), 65%: 35% (P4), and 80% : 20% (P5).  The data obtained were tested for homogeneity with the Barlett test and additional data were tested with the Tuckey test, then the data were analyzed for variance (ANARA) to determine the effect between treatments. The data will be analyzed further with the Least Significant Difference Test (LSD) at 5% level.  The results showed that the addition of mocaf flour and tapioca had an effect on the moisture content, ash content, hardness, cohesiveness, springiness, texture and overall acceptance of baji-baji fish nuggets. The best concentration of mocaf flour and tapiocaadded in baji-baji fish nuggets was P2 (35% mocaf flour: 65% tapioca) with moisture content (53.28%), ash content (2 ,08%), hardness 253.06 gf, cohesiveness 1.01 gs, springiness 6.85 mm, texture 8.56 (solid, compact), taste 7.08 (fish-spesialize), color 7.06 (liked),entirely- acceptance 7.10 (liked), protein content (14.12%), and fat content (10.28%).